Outcomes of gastrointestinal cancer surgeries in Parkinson's disease patients: A nationwide study. (March 2022) - Kodama, Satoshi; Jo, Taisuke; Yasunaga, Hideo; Michihata, Nobuaki; Matsui, Hiroki; Kumazawa, Ryosuke; Shirota, Yuichiro; Fushimi, Kiyohide; Toda, Tatsushi; Hamada, Masashi
Abstract: Background: Parkinson's disease (PD) patients with comorbid cancers are increasing in aging populations. However, little is known about the impact of PD on the outcomes of surgeries to resect these cancers. We sought to clarify the association between PD and discharge status of patients who underwent surgery for gastrointestinal cancers, as the most prevalent malignant neoplasms worldwide. Methods: We identified patients who underwent surgery for gastric and colorectal cancers between April 01, 2014 and March 31, 2018 using the Diagnosis Procedure Combination database, a nationwide administrative inpatient database in Japan. We then collected data on their sex, age, smoking status, body mass index, activities of daily living, cancer stage, and comorbidities. Multivariable Cox regression analyses were conducted to determine factors that influenced discharge to home. Results: Compared with non-PD patients (n = 272, 668), PD patients (n = 1341) were significantly older and less likely to receive laparoscopic surgery, and had lower body mass index, more advanced cancer stage, and lower activities of daily living. The proportions of PD and non-PD patients discharged to home were 80.3% and 96.2%, respectively. The adjusted hazard ratio for discharge to home for PD patients was 0.68 (95% confidence interval, 0.64–0.73; P < 0.001). Conclusions: Compared with non-PD patients, PD patients were less likely to be discharged to home after surgery for gastrointestinal cancers. The present results may indicate a necessity to improve perioperative care for patients with PD. Highlights: Age-related comorbidities such as malignancy is important for Parkinson's disease (PD) patients. Using a nationwide database, we investigated the association between PD and outcomes of gastrointestinal cancer surgeries. PD patients were less likely to be discharged to home after surgery for gastrointestinal cancers. Clinicians are required to improve the perioperative care of PD patients.